Combining MRI and muscle biopsy improves diagnostic accuracy in subacute‐onset idiopathic inflammatory myopathy. Issue 2 (February 2015) - Van De Vlekkert, Janneke; Maas, Mario; Hoogendijk, Jessica E.; De Visser, Marianne; Van Schaik, Ivo N.
ABSTRACT Introduction: In 10–20% of patients with subacute‐onset idiopathic inflammatory myopathy (IIM), muscle biopsy is normal or shows nonspecific findings. MRI can be used as a triage test before muscle biopsy and as an add‐on test if the biopsy is nondiagnostic. Methods: MRI scans of skeletal muscles and muscle biopsies were evaluated prospectively in 48 patients suspected to have IIM. The interpretations of MRI and muscle biopsy were compared with the definite diagnosis (based on European Neuromuscular Centre criteria and response to corticosteroids). Results: The false negative rate (FNR) of all muscle biopsies was 0.23. Biopsies of a muscle showing hyperintensity on MRI (as triage test) had an FNR of 0.19. The result of MRI as an add‐on test in patients with a nondiagnostic muscle biopsy decreased the FNR from 0.23 to 0.06. Conclusions: We recommend both MRI and muscle biopsy in patients suspected of having IIM. Muscle Nerve51: 253–258, 2015